Effect of Semi‐Fluorinated Alkyl Side Chains on Conjugated Polymers with Planar Backbone in Organic Field‐Effect Transistors. Issue 23 (17th August 2018) - Lee, Min‐Hye; Kang, Minji; Jeong, Hyung‐Gu; Park, Jong‐Jin; Hwang, Kyoungtae; Kim, Dong‐Yu
Abstract: Newly synthesized donor–acceptor (D–A) type of conjugated copolymer (PCTV‐BTzF) with semi‐fluorinated alkyl side chains, which has good solubility in common organic solvents, is described. Unlike polymers with hydrocarbon‐based alkyl side chains, semi‐fluorocabonated polymer leads to intriguing results. First, the self‐organization behavior of the semi‐fluoroalkyl side chains by the self‐aggregate propensity between hydrocarbon and fluorocarbon induces patterned microstructural morphology in polymer films; second, it dominates the molecular orientation of polymers with planar back structure. Such unusual properties of the polymer with semi‐fluoroalkyl side chains compared to that with the hydrocarbon ones are verified and characterized though various systematic characterizations, including temperature‐dependent UV–Vis absorption spectroscopy, atomic force microscopy, and 2D‐grazing incident X‐ray diffraction measurement. As a result, PCTV‐BTzF‐based OFETs show the maximum p ‐type field‐effect mobility of 1.02 cm 2  V −1  s −1 in the 200 °C annealed films. Abstract : A conjugated polymer with semi‐fluorinated alkyl chains is successfully synthesized as an organic semiconductor. The polymer, PCTV‐BTzF, forms a self‐assembled microstructure by the self‐aggregating behavior of its semi‐fluorinated alkyl chains. As a result, it shows the optimized charge‐carrier mobility of 1.02 cm 2  V −1  s −1 for holes in field‐effect transistors.